PARALABRAL CYSTS – DIAGNOSIS BY MAGNETIC RESONANCE: PARALABRAL CYSTS - Mallmann , Ralff (2023)
Paralabral cysts, also named paraglenoid labral cysts, are just-articular cystic lesions that usually show a close relationship with the glenoid labrum – they may represent synovial cysts, ganglions cysts, or pseudocysts. Paralabral cyst of the shoulder joint can be observed in 2-4% of the general population, particularly in men during the third and fourth decade. In 79-89% they are related to labral tears, especially SLAP lesions. The symptoms of a paralabral cyst may be the result of rotator cuff disease, labral disease, and entrapment syndrome from compression of the suprascapular nerve (rare cause – cyst must be larger than 1 cm), instability, or a combination of these conditions. Diagnosis is usually made using MRI, with or without arthrography, although ultrasound and computed tomography (CT scan) also have been used for diagnosis. Keywords: Magnetic Resonance Imaging; Shoulder Joint; Shoulder Injuries